Circulating cytokines allow for identification of malignant intraductal papillary mucinous neoplasms of the pancreas. (24th July 2022) - Pu, Ning; Chen, Qiangda; Zhang, Jicheng; Yin, Hanlin; Wang, Dansong; Ji, Yuan; Rao, Shengxiang; Kuang, Tiantao; Xu, Xuefeng; Wu, Wenchuan; Lou, Wenhui
Abstract: Background: Intraductal papillary mucinous neoplasms (IPMNs) are the precursor lesions of pancreatic cancers, requiring active surgical intervention during cancer development. However, the current criteria for predicting malignant IPMNs remain challenging and limited. Hence, this study aimed to assess the discriminatory performance of circulating cytokines, including TNF‐α, IL‐2R, IL‐6, and IL‐8, then build a novel predictive model to improve the diagnostic accuracy. Method: A total of 131 retrospective (from March 2016 to December 2019) and 53 prospective (from March 2020 to January 2021) patients who were histologically confirmed as IPMNs were consecutively collected and analyzed. Result: The circulating levels of TNF‐α, IL‐2R, IL‐6, and IL‐8 were significantly elevated in malignant IPMNs, and were verified as independent factors for malignant IPMNs ( p < 0.05). Then, a novel score, the circulating cytokine score (CCS), was calculated and demonstrated as an independent predictive indicator with a higher area under the curve (AUC) than each cytokine alone ( p < 0.001). Besides the CCS, two high‐risk stigmata features, the presence of solid component (PSC), and main pancreatic duct (MPD) dilation ≥10 mm were also demonstrated as independent indicators for predicting malignant IPMNs. Finally, a novel nomogram incorporating the CCS and these two high‐risk stigmata features presented a remarkable diagnostic performance, both in the training and validation cohorts with AUCs of 0.928 and 0.873, respectively. Conclusion: The CCS can be considered a novel independent predictive indicator for malignant IPMNs. Additionally, the formulated nomogram model integrating the CCS, PSC, and MPD ≥10 mm can be a valuable and promising tool for predicting the malignant transformation of IPMNs during long‐term follow‐ups to assist in timely and accurate surgical decisions. Abstract : The serum TNF‐, IL‐2R, IL‐6, and IL‐8 in malignant IPMNs are significantly higher than benign ones. Circulating cytokine score (CCS) was calculated and proved as an independent predictor.A novel nomogram incorporating CCS showed a remarkable diagnostic performance for distinguishing malignant IPMNs.